2012
DOI: 10.1515/awutp-2015-0003
|View full text |Cite
|
Sign up to set email alerts
|

Bending Of Adsorbed FCN And FNC Molecules Induced By The Renner-Teller Effect

Abstract: It is shown that the bending of FCN and FNC molecules adsorbed on Si (100) -(2 × 1) surface, is due to the Renner-Teller effect induced by the orbital charge transfers by adsorption. From ab initio calculations of free FCN and FNC and the molecules adsorbed on the model Si 9 H 12 cluster, the orbital charge transfers to and from the molecules were calculated, the vibronic coupling constants were estimated, and the curvature K of the adiabatic potentials for the bending coordinate of adsorbed molecules was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…It is based on an approximate evaluation of the Jahn-Teller effect (JTE), pseudo JTE (PJTE), and Renner-Teller effect (RTE) induced by the orbital charge transfers (OCTs) in such systems. This theoretical approach proved to be effective and predictable in rationalization of experimental data regarding the distortion of coordinated molecules [9][10][11]. It was shown that in-plane b 2 -type distortion of ketene molecule, coordinated in the complex (I) is explained as due to the PJTE induced by the back donation to its LUMO 3b 2 (π CO *).…”
Section: Introductionmentioning
confidence: 99%
“…It is based on an approximate evaluation of the Jahn-Teller effect (JTE), pseudo JTE (PJTE), and Renner-Teller effect (RTE) induced by the orbital charge transfers (OCTs) in such systems. This theoretical approach proved to be effective and predictable in rationalization of experimental data regarding the distortion of coordinated molecules [9][10][11]. It was shown that in-plane b 2 -type distortion of ketene molecule, coordinated in the complex (I) is explained as due to the PJTE induced by the back donation to its LUMO 3b 2 (π CO *).…”
Section: Introductionmentioning
confidence: 99%